Satellite Glial Cells in Pain Research: A Targeted Viewpoint of Potential and Future Directions - Gazerani, Parisa (Frontiers in Pain Research, 2021)
Chronic pain has been recognized to occur as a result of sensitization within the pain circuits. An imbalance occurs between excitatory and inhibitory transmission that promotes this sensitization to form. Besides neurons, contribution of the central glia, in particular astrocytes and microglia in the pathogenesis of pain induction and maintenance, has been identified. This has led to targeting astrogliosis and microgliosis to restore normal functions of astrocytes and microglia to help with reversing chronic pain. The role of glia in the peripheral nervous system has been less investigated. Accumulating evidence, however, points to contribution of satellite glial cells (SGCs) to chronic pain. Hence, understanding the potential role of these cells and their interaction with sensory neurons could provide further insights into mechanisms underlying pain signaling that will eventually provide future therapeutic options to target pain. Here, a viewpoint will be presented to the potential future directions in pain research with a focus on SGCs to trigger further research. Promising avenues and new directions include potential use of human iPSC cell lines, cell live imaging, computational analysis, 3D tissue prints and new markers for better understanding of peripheral glia, investigation of glia-glia and macrophage-glia in addition to neuron-glia interactions, the time course of glial activation under acute and chronic pathological pain conditions compared with spontaneous pain, pharmacological and non-pharmacological responses of glia, and potential restoration of normal function of glia considering sex related differences in human tissue, and non-human models.